SIFAT FISIK MEKANIK PAPAN PARTIKEL JERAMI PADI - Gultom, Lastri Anita; hamsyah, Dir; Setyawati, Dina (JURNAL HUTAN LESTARI, 2013)
This research is aimed to know the effect of material composition and concentration of adhesives to physical and mechanical properties particle board. The factors were used includes material composition and content of adhesives urea formaldehyde (UF) on particleboard. Factors material composition consist of three treatment those were 450 g, 540 g, 630 g and content of adhesives factor consist of three treatments is 12%, 14%, and 16%. Particleboard made measuring 30 cm x 30 cm x 1 cm, with compression heat at a temperature 140 C with a the pressure 27 kgf/cm2 for 10 minutes. The mean results of testing the physical and mechanical properties obtained moisture content (9.33% - 12.77%), density (0.44 g/cm3 - 0.54 g/cm3), development of a thick (27.83% - 47 , 95%), water absorption (118.20% - 211.89%), MOE (68.54 kg/cm2 - 539.19 kg/cm2), MOR (13.33 kg/cm2 - 28.35 kg / cm2), internal bonding strength (0.19 kg/cm2 - 0.35 kg/cm2) and a strong hold screws (6.40 kg - 12.02 kg). Results of the study stated particleboard the produced was affected by the amount of material composition and content of the adhesive used.The results of all test physical and mechanical properties that do not comply JIS A 5908 - 2003 except for water content and density of board the produced . Key words :rice straw, particleboard, composition, adhesives, physical mechanical properties